A long-distance translocation initiated an outbreak of raccoon rabies in Hamilton, Ontario, Canada. - Susan Nadin-Davis; Tore Buchanan; Larissa Nituch; Christine Fehlner-Gardiner (Public Library of Science (PLoS), 2020)
Despite proactive measures to prevent raccoon rabies entering Canada from the United States, several incursions of this disease have occurred. The largest outbreak, first reported in December 2015 in the city of Hamilton, Ontario, has resulted in the reporting of 449 animal cases as of December 31, 2018. Initial phylogenetic studies on the index case suggested that this outbreak was not due to local cross-border spread from the Niagara region of the United States where raccoon rabies has persisted for several years. Phylogenetic analysis of whole genome sequences of a viral collection from the Hamilton area and several US states indicates that a long-distance translocation of a diseased animal from southeastern New York State was responsible for this incursion. The role of the skunk as a potential secondary host supporting persistence and / or spread of the virus is also examined.